In Silico Analysis of C-Type Lectins as Co-Infection Receptors of Dengue and Chikungunya Viruses in Aedes aegypti - Sazali, Munawir; Soesilohadi, R. C. Hidayat; Wijayanti, Nastiti; Wibawa, Tri; Ansori, Arif Nur Muhammad (Makara Journal of Science, 2024)
Aedes aegypti is a primer vector of dengue virus (DENV) and chikungunya virus (CHIKV). The susceptibility of mosquitoes to DENV and CHIKV depends on their recognition receptor of pathogens. C-type lectins (CTLs) are an important mediator of virus infection in A. aegypti. This study aims to identify potential receptors and determine the binding affinity between ligand–receptor interaction, CTLs and virus envelopes (DENV-1, 2, 3, and 4 and CHIKV) interaction based on in silico analysis. Sample sequences were obtained from GenBank (NCBI), and 10 CTLs were acquired from VectorBase. Homology modeling based on a minimum standard of 20% was processed using the SWISS-MODEL server. Molecule interaction was visualized as tertiary protein structure in PyMol V1.7.4. Homology modeling revealed all 3D protein model scores to be at 20%. The highest homology modeling score of 98.72% is obtained for CHIKV envelope protein (KF925315.1). The CTL GenBank ID: AAEL014382-PA has the lowest score at −1407.20 kcal/mol. The predicted mechanism of DENV-1, 2, 3, and 4 co-infections with CHIKV-1 is through the binding of the viral envelope to the CTL. Interaction analysis showed that the viruses enter through an endocytic mechanism. The results of homology modeling and lowest interaction energy could serve as the basis for in vivo studies on virus co-infection in A. aegypti. This information illustrates that CTL receptors facilitate DENV and CHIKV co-infection in A. aegypti.